1994
DOI: 10.1136/bmj.309.6956.699
|View full text |Cite
|
Sign up to set email alerts
|

Childhood antecedents of schizophrenia and affective illness: social adjustment at ages 7 and 11

Abstract: probably been the acceptability of myalgic encephalomyelitis as a diagnosis. Fatigue scores in our study were strongly correlated with depression scores, and a recent prospective study in general practice has confirmed this relation. 18 Depression as a cause of fibromyalgia is a much debated issue. Persistent pain is a depressing experience. Our finding that the depression score rises with tender point count irrespective of pain status, however, suggests that depression and fatigue may play a part in the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
223
4
15

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 455 publications
(263 citation statements)
references
References 10 publications
21
223
4
15
Order By: Relevance
“…Obstetric complications, low birth weight, intrauterine malnutrition, smaller head circumference, congenital malformations, and maternal influenza during the second trimester are all positively correlated with the development of schizophrenia Kunugi et al, 1996;McNeil et al, 1994;O'Callaghan et al, 1991;Wahlbeck et al, 2001;Watson et al, 1984;Willinger et al, 2001;Wright et al, 1995). Moreover, during childhood and early adolescence, neuro-motor dysfunction, psychological abnormalities, social mal-adjustment, and cognitive problems are observed long before schizophrenia is diagnosed (Done et al, 1994;Jones et al, 1994;Rosso et al, 2000;Walker et al, 1993Walker et al, , 1994. These early clinical and psychological observations suggest that schizophrenia is a neurodevelopmental disorder that starts prenatally and progresses throughout childhood and adolescence.…”
Section: Schizophrenia As a Neurodevelopmental Disorder: Role Of Glutmentioning
confidence: 99%
“…Obstetric complications, low birth weight, intrauterine malnutrition, smaller head circumference, congenital malformations, and maternal influenza during the second trimester are all positively correlated with the development of schizophrenia Kunugi et al, 1996;McNeil et al, 1994;O'Callaghan et al, 1991;Wahlbeck et al, 2001;Watson et al, 1984;Willinger et al, 2001;Wright et al, 1995). Moreover, during childhood and early adolescence, neuro-motor dysfunction, psychological abnormalities, social mal-adjustment, and cognitive problems are observed long before schizophrenia is diagnosed (Done et al, 1994;Jones et al, 1994;Rosso et al, 2000;Walker et al, 1993Walker et al, , 1994. These early clinical and psychological observations suggest that schizophrenia is a neurodevelopmental disorder that starts prenatally and progresses throughout childhood and adolescence.…”
Section: Schizophrenia As a Neurodevelopmental Disorder: Role Of Glutmentioning
confidence: 99%
“…Reduced social interaction has been reported in this model prior to and after puberty, although this effect does not appear to respond to clozapine treatment 181 . This may be relevant in light of studies showing that prodromal individuals demonstrate difficulties in establishing friendships and emotional bonding 5,[182][183][184] . Molecular studies have shown increased AMPA receptor (GRIA3) levels in the prefrontal cortex of ventral hippocampal lesion rats, which may be the cause of striatal dopaminergic hyperactivation 185,186 .…”
Section: Neonatal Hippocampal Lesionmentioning
confidence: 99%
“…However, the only large-scale prospective birth cohort study examining childhood predictors for later PHT with a follow-up extending to adulthood is the UK National Child Development Study (UKNCDS) [8]. The study included 131 inpatients and 1385 randomly selected controls.…”
Section: Introductionmentioning
confidence: 99%
“…Third, in the UKNCDS, childhood mental health problems relied only on teacher reports at baseline [8]. However, information about childhood problems should be based on standardized tools from several informants to get a comprehensive view of the child's problems [7].…”
Section: Introductionmentioning
confidence: 99%